Web-Based Hotel Inventory Information System at Guna Wijaya Hotel Pati - Dina Surya Shahhilina; Endang Supriyati; Tri Listyorini (SAGA: Journal of Technology and Information System, 2025)
Inventory management at Hotel Guna Wijaya currently relies on manual ledgers, leading to inaccurate real-time data and risks of record loss. Key challenges include difficult stock monitoring and delayed reporting due to manual recapitulation. This study develops a web-based inventory information system to enhance transparency, stock accuracy, and reporting efficiency using the Waterfall model: requirements analysis, system design, implementation, and testing. System design utilized Unified Modeling Language (UML), while testing employed Black Box and User Acceptance Testing (UAT) focusing on Role-Based Access Control (RBAC). Results demonstrate that the system successfully prevents data duplication through a Double-Check Validation feature on item names and locations. The digitalization significantly reduces report generation time from days to seconds using a Reporting Engine integrated with WhatsApp and Email. Furthermore, the Safety Stock Alert feature effectively provides early warnings to prevent shortages. Overall, the system improves monitoring, maintains data integrity, and supports efficient managerial decision-making at Hotel Guna Wijaya.